Estimating children's Active School Travel behaviour using the ROute Observation for Travelling to School (ROOTS) instrument. (December 2021) - Vasey, Thomas V.; Carroll, Suzanne J.; Daniel, Mark; Cargo, Margaret
Abstract: Introduction: Active School Travel (AST) programs, such as Safe Routes to School (SR2S), have been predominantly evaluated using self-reported methods that are susceptible to bias (e.g., social desirability). Objective methods, such as observational route counts, are underutilised in AST program evaluations, and existing studies have not assessed instrument inter-rater reliability. This study aimed to strengthen the evidence base supporting the use of objective measurements to estimate school children's AST behaviour by adapting an existing observational route counting instrument to align with the route-level aims of SR2S programs and assessing its inter-rater reliability. Methods: The ROute Observation for Travelling to School (ROOTS) instrument was adapted from Crawford and Gerrard's Ride2School instrument. Reliability data were collected across four days from three purposively selected public primary schools (one school per day with one school repeated due to rain). Four pairs of trained observers were assigned to different routes at observation points approximately 100–200m away from the same school on the same day. Without conferring, the observational pairs recorded all active travel behaviour (i.e., children walking, cycling, scootering, skating to school), for four 15-minute intervals between 8:15am and 9:15am. Intraclass Correlation Coefficients (ICC) were computed to assess the inter-rater reliability of each observational pair. Results: The total number of observations made by the four observational pairs was 353.0 (M = 88.3, SD = 27.1). ICCs for observational pairs ranged between 0.841 (95% CI: 0.758, 0.897) and 1.000, reflecting good to excellent inter-rater reliability. Conclusion: The ROOTS instrument had good to excellent inter-rater reliability, which supports the use of observational route counts to provide AST evaluations with an objective, reliable alternative to self-reported methods. The ROOTS instrument may be particularly useful for researchers and practitioners evaluating route-level AST behaviour in SR2S programs to tailor these programs to the route-level needs of children and parents. Highlights: First observational route counting instrument to align with the aims of Safe Routes to School programs. Offers researchers and practitioners with a reliable alternative to self-reported methods. Can inform the design and tailoring of programs to the route-level needs of children and parents.